Recent Advances in Electrospun Sustainable Composites for Biomedical, Environmental, Energy, and Packaging Applications - Liu, Hao; Gough, Christopher R.; Deng, Qianqian; Gu, Zhenggui; Wang, Fang; Hu, Xiao (International journal of molecular sciences, 2020)
Electrospinning has gained constant enthusiasm and wide interest as a novel sustainable material processing technique due to its ease of operation and wide adaptability for fabricating eco-friendly fibers on a nanoscale. In addition, the device working parameters, spinning solution properties, and the environmental factors can have a significant effect on the fibers’ morphology during electrospinning. This review summarizes the newly developed principles and influence factors for electrospinning technology in the past five years, including these factors’ interactions with the electrospinning mechanism as well as its most recent applications of electrospun natural or sustainable composite materials in biology, environmental protection, energy, and food packaging materials.